Cardinal Role of the Intrarenal Renin-Angiotensin System in the Pathogenesis of Diabetic Nephropathy. (1st February 2013) - Kobori, Hiroyuki; Kamiyama, Masumi; Harrison-Bernard, Lisa M.; Navar, L. Gabriel
Abstract : Diabetes mellitus is one of the most prevalent diseases and is associated with increased incidence of structural and functional derangements in the kidneys, eventually leading to end-stage renal disease in a significant fraction of afflicted individuals. The renoprotective effects of renin-angiotensin system (RAS) blockade have been established; however, the mechanistic pathways have not been fully elucidated. In this review article, the cardinal role of an activated RAS in the pathogenesis of diabetic nephropathy (DN) is discussed with a focus on 4 themes: (1) introduction to RAS cascade, (2) intrarenal RAS in diabetes, (3) clinical outcomes of RAS blockade in DN, and (4) potential of urinary angiotensinogen as an early biomarker of intrarenal RAS status in DN. This review article provides a mechanistic rational supporting the hypothesis that an activated intrarenal RAS contributes to the pathogenesis of DN and that urinary angiotensinogen levels provide an index of intrarenal RAS activity.